2015
DOI: 10.1038/srep14024
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-wide analysis of chromium-stress responsive microRNAs to explore miRNA-mediated regulatory networks in radish (Raphanus sativus L.)

Abstract: MicroRNAs (miRNAs) are small noncoding RNAs that play pivotal roles in plant growth, development and stress response. Chromium (Cr) is one of common environmental contaminants possessing potential health hazards to living organisms. To date, little is known about the regulatory roles of miRNAs in response to Cr stress in radish. To systematically identify Cr-responsive miRNAs and their targets in radish, two sRNA libraries derived from Cr-free (CK) and Cr-treated (Cr200) roots were constructed. With Solexa seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 58 publications
4
33
0
Order By: Relevance
“…To further obtain an overview of these biological processes altered during H. glycines infection, the core DEGs were assigned to KEGG pathways, as previously described 19 . In total, eight and six KEGG pathways were over-represented for up- and down-regulated DEGs, respectively (Table S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…To further obtain an overview of these biological processes altered during H. glycines infection, the core DEGs were assigned to KEGG pathways, as previously described 19 . In total, eight and six KEGG pathways were over-represented for up- and down-regulated DEGs, respectively (Table S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Microarray analysis in Glycine max led to the identification of 26 Cd-responsive miRNAs (Fang et al, 2013). Solexa sequencing in radish (Raphanus sativus) identified 54 known and 16 novel miRNAs that were differentially expressed under Cr stress (Liu et al, 2015). Deep sequencing in the Cd hyperaccumulator Sedum alfredii identified 356 miRNAs, of which 79 miRNAs were differentially expressed under Cd stress (Han et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidences have revealed that proteomic studies are playing important roles in the post-genomic era for characterizing the molecular mechanisms underlying plant responses to HM stresses (Fukao et al, 2011; Wang et al, 2013, 2014; Sebastiani et al, 2014). Radish is an important root vegetables worldwide, which has been considered as one of the most significant root species for dissecting the molecular regulatory network of HM stress in Brassicaceae crops (Xu et al, 2012; Wang et al, 2014, 2015a; Liu et al, 2015; Xie et al, 2015). In the current study, comparative proteomics analysis by iTRAQ together with other-omics techniques reveals complex regulatory network and provides insights into the response of radish root under Pb exposure.…”
Section: Discussionmentioning
confidence: 99%